Comparative Analysis of Sales, Gross Profit and GPM Before After the Increase in Vat in the Industrial Sector 2020-2024 - Apriyanti, Nur Ulyana; Mukhzarudfa, Mukhzarudfa; Tiswiyanti, Wiwik (Asian Journal of Management Analytics, 2025)
This study aims to perform a comparative analysis of sales levels, gross profit, and GPM before and after the increase in the (VAT) rate in companies listed on the IDX from 2020 to 2024. This is a comparative study using a quantitative approach. The data used in this research is secondary data, obtained from financial reports of companies listed on the IDX for the years 2020-2024.Sampling in this study was conducted using a purposive sampling technique, resulting in 32 companies from a population of 66 that met the criteria. The technique used to analyze the comparison of sales levels, gross profit, and GPM before and after the VAT rate increase is the Wilcoxon Signed Rank Test. The analysis reveals a significant difference in sales levels and gross profit, while no significant difference was found in the GPM before and after the VAT rate increase in the companies listed on the IDX.The results of the study indicate a significant difference in sales levels and gross profit before and after the VAT rate increase.